De tribus principiis, oder, Beschreibung der drey Principien göttliches Wesens : Of the three principles of divine being, 1619 - Weeks, Andrew, 1947-; Weeks, Andrew, 1947-; Böhme, Jakob, 1575-1624.; Böhme, Jakob, 1575-1624. (Aries Book Series, 2019)
Jacob Boehme's Of the Three Principles of Divine Being, 1619, is vital for understanding his work as a whole, its relationship to its epoch, and its role in intellectual history. Reproduced here using the methods of critical edition, the original of the work and its adjacent translation, together with an extensive introduction and commentary, provide unprecedented access to this essential work of early modern thought and cast a fresh light on the revolutionary theological, philosophical, and scientific developments coinciding with the start of the Thirty Years' War. The 1730 edition is annotated with reference to the manuscript sources to clarify ambiguities so that the translation can interpret the text without refracting its meaning. This makes it possible to interpret Boehme's complex theories of the origin of the divine being and of nature, the human creature, and the female aspect of divinity.